Respuesta :

Answer:

f−1(x) = [tex]\frac{4x}{6}[/tex]

Step-by-step explanation:

f(x) = 0.25(6)x, find f−1(x).

f(x) = 0.25(6)x

f(x) = [tex]\frac{6}{4}[/tex]x = [tex]\frac{6x}{4}[/tex]

f(x) = y

y =  [tex]\frac{6x}{4}[/tex]

Substitute y for an x & x for a y

x = [tex]\frac{6y}{4}[/tex]

Multiply both sides by 4

4( x ) = 4( [tex]\frac{6y}{4}[/tex] )

4x = 6y

Divide both sides by 6 to solve for y

[tex]\frac{4x}{6}[/tex] = y

y = [tex]\frac{4x}{6}[/tex]

so f−1(x) = [tex]\frac{4x}{6}[/tex]

ACCESS MORE